Evidence-based public health - Brownson, Ross C. (New York ; Oxford : Oxford University Press, 2011)
The authors deal not only with finding and using scientific evidence, but also with implementation and evaluation of interventions that generate new evidence on effectiveness. Each chapter covers the basic issues and provides multiple examples to illustrate important concepts.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 10, 2011).
Keywords: Public health; Evidence-based medicine